Codecomposition of a Transformation Semigroup - Hosseini, A.; Sabbaghan, M.; Shirazi, F. Ayatollah Zadeh (Ukrains’kyi Matematychnyi Zhurnal, 2013)
The present paper deals with the concept of “codecomposition” of a transformation semigroup interacting with the phase semigroup. In this way, we distinguish new classes of transformation semigroups with meaningful relations, e.g., we show the class of all distal transformation semigroups ⊂, the class of all transformation semigroups decomposable into distal semigroups ⊂, and the class of all transformation semigroups (here, ⊂ is strict inclusion).